Análise dos efeitos da conservação ambiental e da exploração petrolífera na vida dos camponeses do Páramo de Tota - Rojas Arias, Andrés Felipe (2024)
The aim of this article is to show how the intrinsic relationship between the peasants of Tota (Boyacá, Colombia) and the paramo ecosystem they inhabit is being negatively affected by policies of both oil extraction and environmental protection. The qualitative research employed includes interviews with local peasants, review of public policies, historical analysis of colonial influence on the perception and treatment of land, and case studies to illustrate peasants' experiences with extractivist and environmental policies. The results show that the peasants of Tota, heirs to the ancestral knowledge of the Muisca, are stigmatized and marginalized by technocrats influenced by Eurocentric ideologies, who see peasants as obstacles to progress, like the stigmatization suffered by their indigenous ancestors during the conquest. Public policies favor oil companies and state institutions that protect water, not for the benefit of peasants, but to guarantee the future of these industries. The discussion highlights how Eurocentric policies continue to perpetuate the exploitation and marginalization of peasants, ignoring the intrinsic value of the paramo and its importance for peasant life. Thus, public policies must be reformulated to integrate the perspectives and needs of peasants, promoting a more holistic and integrated approach.